Policy-Based Green Accounting in Basic Education Institutions in Low-Income Countries: Contributions and Missing Dimensions - Reuben Bihu (Scientia Publica Media, 2026)
In this paper, I argue that green accounting in basic education institutions in low-income countries receives an inevitable priority in policy innovation demands currently. The paper analyses the contributions and salient gaps in the implementation of selected environmental conventions, protocols, and policy frameworks, and local priorities for green accounting in basic education institutions. The analysis is grounded in economic theory and affirms the Sustainable Development Goals (SDGs). An online ethnographic review was used to collect and systematically analyse 26 documents, including 7 environmental conventions, 3 related protocols, 1 local policy, and 15 related research publications gathered using the PRISMA approach. The analysis reveals that green accounting faces a parochial place in the implementation of environment-affecting programmes in basic education institutions of low-income countries. This situation results from inadequate local institutional capacity in terms of finances, technicalities, and technologies necessary to comply with the contentions of implemented documents. Consequently, despite the high proportions of ratifications of the documents by the State parties, environmental conservation, protection, and rehabilitation goals are not realised to the expected extent. It is imperative that the eco-environmental economic cost implications of running basic education institutions be accounted for, and there are adjustments in policy frameworks to facilitate environmental performance in local institutions.